Sanksi Pidana terhadap Para Pemasang dan Promosi Iklan Bermuatan Konten Judi Online - Pande Putu Rastika Paramartha; Anak Agung Sagung Laksmi Dewi; I Putu Gede Seputra (Warmadewa Press, 2021)
Online gambling is a phenomenon that cannot be denied and is found in the community. In promoting online gambling, site owners usually advertise their online gambling sites to internet. Because this is the dissemination and development of online gambling sites is growing rapidly. From the above background, the problem can be formulated as follows: How is the regulation of criminal sanctions against the installer and promotion of online gambling advertisements and What are the criminal sanctions against the installer and promotion of online gambling advertisements The research method used is the type of normative research that is the type of research by conducting its assessment based on legal materials from the prevailing literature and legislation. The legal arrangements for advertisers and promotions of online gambling are regulated in Law Number 11 of 2008 concerning Electronic Information and Transactions in article 27 paragraph 2 which reads: